2007
DOI: 10.3748/wjg.v13.i22.3090
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of diagnostic findings and scoring systems in outcome prediction in acute pancreatitis

Abstract: AIM:To determine factors related to disease severity, mortality and morbidity in acute pancreatitis. METHODS:One hundred and ninety-nine consecutive patients were admitted with the diagnosis of acute pancreatitis (AP) in a 5-year period (1998)(1999)(2000)(2001)(2002). In a prospective design, demographic data, etiology, mean hospital admission time, clinical, radiological, biochemical findings, treatment modalities, mortality and morbidity were recorded. Endocrine insufficiency was investigated with oral gluco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
49
1
3

Year Published

2008
2008
2017
2017

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(58 citation statements)
references
References 29 publications
(53 reference statements)
5
49
1
3
Order By: Relevance
“…Many systems have been used to predict the severity and prognosis of pancreatitis at an early stage, but none 210 Table 2. Ranson score and CRP value relation with the severity of acute pancreatitis of these systems has been proven to be perfect (16). Various models have been defined based on clinical, laboratory and radiological findings.…”
Section: Discussionmentioning
confidence: 99%
“…Many systems have been used to predict the severity and prognosis of pancreatitis at an early stage, but none 210 Table 2. Ranson score and CRP value relation with the severity of acute pancreatitis of these systems has been proven to be perfect (16). Various models have been defined based on clinical, laboratory and radiological findings.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, Kaya [20] demonstrated that the APACHE Ⅱ score is the best predictor of mortality among Ranson, Imrie and APACHE Ⅱ scores. We found that both APACHE Ⅱ and Ranson's criteria were of significance in predicting mortality in the aged.…”
Section: Discussionmentioning
confidence: 99%
“…It was analysed in 7 studies [24,31,33,34,[37][38][39] . Among them, three used the ROC curves [24,33,39] , three investigated the correlation between mortality and the classes defined [31,34,38] , and one calculated the odds ratio of mortality when CTSI was 6 5 [37] . PPV was 41%, NPV 92% [33] .…”
Section: Radiological Scoresmentioning
confidence: 99%